Health Behavior Changes Through Television: The Roles of De Facto and Motivated Selection Processes - Flay, Brian R.; McFall, Stephanie; Burton, Dee; Cook, Thomas D.; Warnecke, Richard B. (Journal of health and social behavior, 1993)
We assess the role played by two types of self-selection in accounting for the influence of a television series on smoking cessation. De facto selection is based on respondents' regular channel viewing habits that can expose them to the series. Motivated self-selection takes place when viewers deliberately select to watch television programming because it meets their desire to quit smoking. Self-selection also can be viewed as a methodological artifact, spuriously accounting for the association between the airing of the series and smoking cessation among the target audience. Subjects were a probability sample of Chicago smokers who regularly watch the evening news on one of the network channels. The intervention was a televised self-help smoking cessation program broadcast on one of the network channels over 20 days. Using nested covariance structure models for the analysis, we conclude that 1) de facto selection had no influence on exposure to the program; 2) motivated selection had no influence on exposure to the program; 3) the program reduced smoking; and 4) this effect cannot be attributed solely to the methodological artifact of self-selection, although motivation to quit smoking did have the strongest influence on attempts to quit.